Mathematics placement test score & its significance: a case study - Sathissan Ragavan, * (Sunway College KL, 2015)
The aim of this study is to examine the relationship between Mathematics placement test scores and students’ final scores in Mathematics course. Questions have been raised before regarding the importance of Mathematics placement tests in placing students into the most suitable Mathematics course. The study examines the importance of the Mathematics placement test and its significant contribution to students’ performance in Mathematics course taken at their pre university level of studies. Mathematics placement tests undeniably fulfil their purpose of providing preliminary Mathematics course placement recommendations, encouraging students to register themselves for the most appropriate Mathematics course based on their competence, thus helping students to perform better. The study will focus on the 86 students enrolled in Monash University Foundation Year (MUFY) at Sunway College Johor Bahru in 2013. The correlation and regression between their Mathematics placement test scores and their final marks in the MUFY Mathematics Unit 1 (equivalent to year 12 Mathematics) and MUFY Fundamental Mathematics Unit 1 (equivalent to year 11 Mathematics) is analysed.